Analysis of Legal Protection for Investors Through The Securities rowdfunding (SCF) Mechanism Based on Law No. 8 of 1995 Concerning Capital Markets (A Study of MBG Funding Through Danamart) - Jimmy Lizardo; Hulman Panjaitan; Paltiada Saragi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The rapid development of Securities Crowdfunding (SCF) as a digital financing mechanism has transformed capital market practices by expanding access to investment and funding. However, this innovation raises critical concerns regarding investor protection, particularly in relation to information disclosure and asymmetry. This study is grounded in the theory of information asymmetry proposed by Akerlof, as well as legal protection and legal certainty theories developed by Hadjon and Mertokusumo, which emphasize the importance of transparency and clear legal standards in safeguarding investor interests. This research employs a descriptive-analytical legal method using a normative juridical approach supported by limited empirical analysis. The study examines the synchronization between Law Number 8 of 1995 on Capital Markets and Financial Services Authority Regulation Number 57/POJK.4/2020, as well as evaluates the quality of material information disclosure in SCF prospectuses, particularly in the funding of the Free Nutritious Meal Program (MBG) through the Danamart platform. The findings reveal that although SCF regulations have formally adopted the disclosure principle, the level of regulatory synchronization remains incomplete. The SCF framework lacks detailed standards for material information disclosure, creating legal uncertainty and reducing the effectiveness of investor protection. Empirical analysis further indicates that disclosure practices tend to emphasize potential returns while providing insufficient detail on risks, thereby sustaining information asymmetry and limiting informed decision-making by retail investors. In conclusion, while SCF enhances financial inclusion and investment opportunities, its effectiveness in protecting investors depends on strengthening disclosure standards, improving transparency, and ensuring regulatory alignment with broader capital market principles.